PRICE PERCEPTION - E. S. Margianti; Trini Saptariani; Hotniar Sirongoringo (Jurnal Ilmiah Ekonomi Bisnis, 2009)
This research is intended to investigate consumer price perception which is set up by two (2) big retail chains. However, research variable is subjected to consumer opinion, so that survey research was deployed to gather data needed. Questionnaire, as research instrument, was distributed to consumers who perform convenience shopping goods at two chains, i.e. Carrefour and Giant in Depok city. As research variables are latent in nature, multilevel structural equation modeling was used to analyze data collected. Result shows that there’s no different price perception between two chains.Key words : perceived price, chain, shopping goods, retailer, consumer